Effectiveness of occupational e-mental health interventions: a systematic review and meta-analysis of randomized controlled trials - Elena A Phillips; Vladimir S Gordeev; Jonas Schreyögg (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVE: This systematic review and meta-analysis investigated the effectiveness of occupational e-mental health interventions aimed at stress, depression, anxiety, burnout, insomnia, mindfulness, well-being, and alcohol misuse and their potential treatment moderators. METHODS: We systematically reviewed randomized control trials published in English using three electronic databases (MEDLINE, PsycINFO, CINAHL) and three register trials. A pooled effect size for each mental health area was calculated using random-effects modelling. For each meta-analysis, we conducted an analysis of potential moderators (ie, type of recruitment, age, gender, initial psychological symptoms, guidance, therapy type, and study quality). RESULTS: In total, 50 studies were included in the systematic review, and 34 studies were included in the meta-analyses. We noted moderate treatment effects on stress (Hedges'g=0.54), insomnia (g=0.70), and burnout (g=0.51) and small treatment effects on depression (g=0.30), anxiety (g=0.34), well-being (g=0.35), and mindfulness (g=0.42). The pooled effect on alcohol intake was small and nonsignificant. CONCLUSIONS: Our results suggest that occupational e-mental health interventions are associated with significant health improvements. However, more research is required to understand which factors contribute to the variation in effectiveness of particular interventions depending on the mental health area and characteristics of participants and interventions.